Renal Function in Children Suffering from Sickle Cell Disease: Challenge of Early Detection in Highly Resource-Scarce Settings - Aloni, Michel Ntetani; Ngiyulu, René Makwala; Gini-Ehungu, Jean-Lambert; Nsibu, Célestin Ndosimao; Ekila, Mathilde Bothale; Lepira, François Bompeka; Nseka, Nazaire Mangani (PloS one, 2014)
The prevalence of Sickle cell disease is extremely high in Democratic Republic of Congo. Despite this high prevalence of the disease, data on renal abnormalities in children are rare. The study proposed to assess blood pressure, glomerular function, urea and uric acid levels in 65 steady state Congolese children with homozygous sickle cell disease and 67 normal controls. In Hb-SS group, blood pressure level tended to be lower than Hb-AA groups but there was no statistically significant difference (p>0.05) between the two groups. The absolute values for GFR corrected for BSA were significantly higher in Hb-SS group compared to Hb-AA group (130.5±34.1 ml/min/1.73 m2 vs 113.7±24.5 ml/min/1.73 m2; p = 0.004). Children with Hb-SS were more likely to hyperfiltrate (30.8% of subjects) than children with Hb-AA (6.1% of subjects). Proteinuria was found in 4 (6.2%) children with Hb-SS. Uric acid level was significantly increased in children with Hb-SS compared to corresponding values in control group (4.4±1.3 mg/dl vs 3.5±1.1 mg/dl; p<0.001). Urea level was significantly decreased compared to corresponding values in Hb-AA group (15.3±8.3 mg/dl vs 22.9±10.1 mg/dl; p<0.001). Hyperfiltration, low creatinine, lower urea and high uric acid are more common in children with sickle cell disease than in normal controls.